Glyoxalase I Ala111Glu gene polymorphism: No association with breast cancer risk but correlated with absence of progesterone receptor - Naidu, R.; Har, Y.C.; Taib, N.A.M. (Blackwell Publishing, 2010)
The aim of the present study was to evaluate the association between the Glyoxalase I (GLOI) Ala111Glu polymorphism and breast cancer risk among the major Malaysian ethnic groups, the Malays, Chinese and Indians, as well as clinicopathological characteristics of these patients. Genotyping of GLOI gene was performed on blood samples obtained from 387 patients and 252 normal healthy women who had no history of any malignancy using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. The genotype and allele frequencies of GLOI polymorphism were not significantly different between the patients and normal individuals among the Malays (P = 0.721, 0.402), Chinese (P = 0.208, 0.079) and Indians (P = 0.612, 0.349), respectively. The Malay, Chinese and Indian women who were Glu/Glu homozygotes (P = 0.419, 0.093, 0.367), Ala/Glu heterozygotes (P = 0.648, 0.182, 0.402) and carriers of Glu allele (P = 0.402, 0.079, 0.349), respectively, were not associated with breast cancer risk. The Glu allele genotype was significantly associated with absence of progesterone receptor (P = 0.036). Thus, the polymorphic variant of the GLOI gene might not be a useful genetic marker to identify Malaysian Malay, Chinese or Indian women who could be at greater risk of developing breast cancer.